Quality of home stimulation and language development in children aged 12-24 months living in orphanages and family homes - Yuridyah P. Mulyadi; Soedjatmiko Soedjatmiko; Hardiono D. Pusponegoro (Paediatrica Indonesiana, 2009)
Background  Language development  is  fundamental for children'sintellectual development. Therefore, early stimulation in thefirst  three  years  of  life play an  important  role especially indisadvantaged communities such  as  foster homes.Objective  To  determine  the  quality  of  home stimulation  andlanguage development, and their correlations in children livingin orphanages  and  family homes.Methods  This study was conducted between December  2007  andJanuary  2008.  Subjects were recruited from several orphanagesin Jakarta, Tangerang, Bogor, also three posyandus in Jakarta andTangerang.  The  quality  of  home stimulation was assessed usingHome  Stimulation  Observation  for  the  Measurement  of  theEnvironment (HOME) scores, while language development wasassessed using Clinical Linguistic and Auditory Milestone ScaleDevelopment  Quotient  (CLAMS  DQ).Results  A total  of  80  healthy children, consisting  of  40  childrenin orphanages  and  40  in family homes were enrolled. Inadequatestimulation and language delay were found  to  be significantlyhigher in the orphanage group  (52.5%  vs.  27.5%; P=0.022  and57.5%  vs.  10%; P<0.001,  respectively).  HOME  Scores  andCLAMS  DQ  were also significantly lower in  the  orphanagegroup compared to those  in  the family home group  (25.6  vs31.5; P<0.001  and  84.0  vs  110.7; P=0.002).  Logistic regressionrevealed  that  caregiver-child  attachment  time was  the  onlyrisk factor  for  language delay  (OR  32.32; P<0.0001),  in  bothorphanages and family homes.Result  The  quality of home stimulation  is  lower in the orphanages,which results in a higher rate  of  language delay  in  children aged12-24  months.